Laminin fragment P1 is increased in the lower respiratory tract of patients with diffuse interstitial lung diseases - Pérez-Arellano, J L; Pedraz, M J; Fuertes, A; de la Cruz, J L; González de Buitrago, J M; Jiménez, A (Chest, 1993)
Laminin is a 900,000-dalton extracellular matrix glycoprotein involved in a variety of functions, including cellular movement, growth, and differentiation. The aim of this work was to investigate the presence and biologic significance of this substance in the bronchoalveolar lavage fluid (BALF) of diffuse interstitial lung diseases (DILD). Levels of laminin fragment P1 (LFP) were measured by radioimmunoassay in BALF and sera from controls (n = 8) and patients with several types of DILD: sarcoidosis (n = 10), neoplastic pulmonary infiltration (n = 8), pulmonary fibrosis (n = 5), and hypersensitivity pneumonitis (n = 5). Furthermore, their relation to signs of alveolitis (cellular profiles and albumin concentration in BALF) and evidence of pulmonary fibroblast activation (BALF aminoterminal propeptide of type III procollagen) was examined. Laminin fragment P1 immunoreactivity was detectable in BALF, even in the control group, but patients with all types of DILD had higher concentrations than the control subjects. The serum levels of LFP were similar in all groups studied. Neutrophil and lymphocyte proportions were significantly higher in all DILD groups than in the control group. A positive correlation was seen between lymphocyte proportion and laminin fragment P1 in BALF. Moreover, in BALF a positive correlation was found between LFP and albumin and between LFP and the aminoterminal propeptide of type III procollagen. The BALF macrophage-associated laminin fragment P1 was significantly higher in the active sarcoidosis subgroup compared with the control group. Thus, laminin is a normal constituent of the epithelial lining fluid. The increase of laminin in BALF of patients with DILD suggests that laminin may contribute to their pathogenesis.